Right retrocaval ureter type 2 with left atrophied kidney: A rare case report - Mustafa I. Al-Shalah; Zaid F. Altawallbeh; Rashed Yousef Al Sharqi; Mohammad kh Alzawahreh; Raed Bassam Abulawi; Mohab Alsaid Saad; Yousif Ahmad Hanafi; Laith Alnajada; Ala' Mohammad Yaser Alfreahat (Urology Case Reports)
Case: A 22-year-old male smoker presented with intermittent right flank pain lasting over a year. He had a history of atrophied left kidney and gout. Physical exam revealed mild right renal angle tenderness. Outcome: Initial imaging, pointed to a diagnosis of ureteropelvic junction stenosis. During surgery, a type two retrocaval ureter was discovered. Transposition pyelo-pyelostomy was performed to repair the ureter, and a double-J stent was inserted. Conclusion: This case highlights the challenge of accurately diagnosing retrocaval ureter, especially type, based on initial radiological images.